2015
DOI: 10.2214/ajr.15.14554
|View full text |Cite|
|
Sign up to set email alerts
|

Solid Renal Cell Carcinoma Measuring Water Attenuation (−10 to 20 HU) on Unenhanced CT

Abstract: A minority of solid RCCs have attenuation similar to that of water on unenhanced CT. In this study, all such tumors were of the clear cell subtype and qualitatively heterogeneous, suggesting they can be distinguished from simple cysts on unenhanced CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 24 publications
1
20
1
Order By: Relevance
“…The detection and characterization of incidentally imaged renal lesions on unenhanced CT remains difficult due to the method’s low soft-tissue contrast 4 . Additionally, unenhanced CT values of different RCC subtypes showed divergent measurements 4 24 . Contrast enhanced multiphasic CT and MRI images are used in clinical routine to diagnose RCC and to define the subtype 5 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The detection and characterization of incidentally imaged renal lesions on unenhanced CT remains difficult due to the method’s low soft-tissue contrast 4 . Additionally, unenhanced CT values of different RCC subtypes showed divergent measurements 4 24 . Contrast enhanced multiphasic CT and MRI images are used in clinical routine to diagnose RCC and to define the subtype 5 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the density of most RCCs has been in the range of 20–70 HU (15). However, a few solid RCCs can show similar attenuation to water (-10–20 HU) on unenhanced CT (18). In our study, none of the RCCs showed water attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…RCCs were a rare (in the 1% range) finding at unenhanced CT and differentiating them from benign cyst on unenhanced CT is difficult in many cases (14). Previous studies have evaluated the characteristic image findings of RCC on unenhanced CT (15)(16)(17)(18); however, over one-third (37%) of potentially detectable cancers were missed or incorrectly interpreted on unenhanced CT (14). Moreover, these studies were not focused on only T1a RCC, which could be done minimally invasive treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have shown that the density of a homogeneous mass on non-contrast CT can safely categorize it as a cyst if region of interest measurements either fall between −10 to 20 HU or are equal to or greater than 70 HU (as a result of proteinaceous or hemorrhagic content) [1417]. A recent study showed that in a population of patients 40–69 years of age, none of the 42 homogeneous masses on non-contrast CT with density values of 21–39 HU proved to be clinically significant after 5 years.…”
Section: Flowchart 1: Incidental Renal Mass On Non-contrast Ctmentioning
confidence: 99%